A treatment program for flat feet and its effect on pain levels in athletes aged 9-15 years - السعدي, م.م مرتضى تحسين جواد; الاؤسي, م.د علي سلام كاظم (Sulaimani Journal for Humanities, 2026)
After a long and arduous journey of research into flat feet and how to correct this deformity, which causes pain during exercise, and based on scientific measurements adopted by the researchers using a foot scan device, fruitful results were achieved. This allowed them to identify the underlying problem and overcome the obstacles and difficulties faced by those with flat feet. This research was further supported by numerous interviews with medical specialists, which helped to resolve many difficulties and confirm the correlation between flat feet and the degree of pain experienced by athletes. This led the researchers to recognize the importance of this problem and the necessity of developing a program to correct this deformity. Based on this work, the research concluded that the further the instep is from the gait path, the greater the angle between the longitudinal axis of the foot and the direction of walking, leading to increased pain for those affected. Similarly, the larger the instep, the greater the pain. Furthermore, any foot deformity that results in an uneven distribution of force between the heel and the insteps leads to increased pain. Based on the aforementioned research and its results, the researchers recommend relying on these therapeutic exercises to correct this deformity, given that the sample group is aged 9-15, i.e., during the growth stage.